The Effect of Budget Planning, Human Resource Competency, and The Budget Implementation Process on Budget Absorption Optimization In The Social Service Agency of Central Java Province - Amelia, Firza; Sunarto, Sunarto (Publikasi Indonesia, 2026)
Budget absorption remains a critical issue in public sector financial management, particularly within regional government agencies in Indonesia. One persistent challenge is the uneven pattern of budget realization, which tends to be low at the beginning of the fiscal year and accumulates toward the end, potentially disrupting public service delivery and program effectiveness. This research examines the influence of budget planning, human resource competency, and budget implementation processes on the optimization of budget absorption. The study was conducted at the Social Service Office of Central Java Province. The research objects included the planning, finance, and technical implementation departments. The sampling method used was purposive sampling, with the research period set for 2025. The relationships and influences among variables were analyzed using multiple regression analysis. The results showed that budget implementation had a significant and positive effect on budget absorption, while budget planning and human resource competency did not show a significant effect. The study concludes that strengthening the budget execution stage—including accelerating administrative processes and enhancing coordination among work units—is essential to improve budget absorption performance. These findings provide valuable insights for regional governments in designing more effective budget management strategies to support public service delivery and community welfare.